Enhancing Critical Thinking in Society 5.0: An Evaluation of High Order Thinking Skills (HOTS) in Secondary Education - Zahri, Triave Nuzila; Syukur, Yarmis; Sari, Azmatul Khairiah; Sari, Resti Elma; Cusinia, Azahra Hardi (International Journal of Research in Counseling and Education, 2023)
The learning process in the Society 5.0 era requires students to develop critical thinking skills. Higher Order Thinking Skills (HOTS) play a crucial role in shaping students into creative, analytical, and independent learners. These skills involve the ability to analyze, evaluate, and generate new ideas. However, many students struggle with HOTS-based learning patterns because they are accustomed to conventional teaching methods. Students who are unprepared for HOTS-based learning find it difficult to adapt to the demands of critical thinking, problem-solving, and analytical skills. This descriptive comparative study aims to evaluate students' learning skills based on HOTS and examine gender-based differences in these skills. The population of this study consists of 879 students from Junior High School Number 30 Padang, with a sample of 265 students selected using stratified random sampling. Data were collected through a Likert-scale questionnaire measuring students' abilities in three sub-variables: completing assignments, answering exams, and participating in learning activities. Descriptive statistical analysis shows that students' mastery of HOTS-based learning skills is 77% in completing assignments, 77% in answering exams, and 76% in participating in learning activities. The results of an independent t-test indicate that female students demonstrate better mastery of HOTS-based learning skills than male students. These findings highlight the importance of schools enhancing students' HOTS-based learning skills to improve academic outcomes and better prepare them for future challenges.